As pesquisas sobre instituições escolares: o método dialético marxista de investigação - Paolo Nosella; Ester Buffa (EccoS – Revista Científica)
Studies on school institutions were developed from 1990s on. Nowadays they represent a significant theme in history, sociology and philosophy of education realm. We developed many investigations about this theme, tracking the main school institutions in the city of São Carlos (SP). Obviously, such a large number of studies require a critical balance in order to verify in which measure their results have contributed to an objective comprehension of the Brazilian school history. Thus, it is a research that presents serious methodological dangers slipping in frequent reductionisms that, unfortunately, we have ascertained, such as: nostalgia, personalism, particularism, ornamental culturalism, laudatory or apologetic description. Keeping this methodological concern, we elaborated, in 2004, a research project approved by CNPq (National Council of Scientific and Technological Development) and that is being developed with the title History and Philosophy in school institutions: evaluation of a research line. We are most interested in verifying the theoretical referential and the most used methodological procedures. In this sense, we ascertained two important characteristics: a frequent incoherence between the proclaimed theoretical referential and the one effectively used in practice, and the fact that many studies emphasize the particular aspects that form the school institution, leaving aside the society that produces it. In order to avoid such gaps, it makes sense to deep the dialectical investigative method which describes the particular in the light of the economical, political, social and cultural context.